A STUDY ON WITNESS PROTECTION LAWS IN INDIA AND THE USA: A COMPARATIVE PERSPECTIVE - Rama; Varshney, Rahul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In order to guarantee Witness protection, an essential part of the criminal justice system, guarantees the safety and security of those who testify against criminals. The United States’ laws pertaining to witness protection and India are compared in this paper ,evaluating their effectiveness, legal frameworks, and implementation challenges. In India, the Witness Protection Scheme serves as the primary mechanism for safeguarding witnesses, 2018, which provides essential measures to protect them from threats and intimidation, whereas the USA has a more structured and long-standing Federal Witness Protection Program (WITSEC). The research examines the procedural safeguards, anonymity provisions, relocation measures, and financial assistance provided in both countries. It also evaluates the impact of these laws on witness participation in criminal proceedings and their role in securing convictions. Furthermore, the study identifies gaps in India’s witness protection mechanisms and suggests reforms based on best practices from the USA. By analyzing case studies and legal precedents, This research emphasizes the necessity of a stronger and more effectively enforced In India, a strong framework for protecting witnesses is necessary to increase the legitimacy of the legal system.